Variableistic Analysis of Number Conversion Mathematical Problems - Ruyani, Siti; Hamdani, Hamdani; Rustam, Rustam; Rifat, Mohammad; Suratman, Dede (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study aims to explore the understanding of students in the Computer and Network Engineering (TKJ) specialization at vocational high schools (SMK) in solving mathematics tests focused on number conversion. The primary objectives are to identify and analyze the errors made by students in converting decimal, binary, octal, and hexadecimal numbers, evaluate their perceptions of the test, and assess their mathematical communication skills. This research employs a mixed-method approach, using quantitative methods to analyze the validity and reliability of the number conversion test instruments, and qualitative methods to delve into students' understanding through content and thematic analysis. The study population consists of TKJ students at SMKN 4 Pontianak, with a purposive sample of 32 tenth-grade students. The findings reveal several common errors, including difficulties in repeated division and digit grouping. Data indicate that 36% of students disagree that they understand decimal to octal conversion, and 18% disagree with decimal to hexadecimal conversion. Students' perceptions of test difficulty vary, with 45% feeling very confident in writing conversion steps, while 30% show significant uncertainty. Additionally, challenges in mathematical communication are evident, such as errors in representation, reading, and writing numbers. The study concludes that there is a need to improve teaching methods and evaluation to enhance students' understanding and skills in number conversion. Recommendations include developing more effective teaching strategies and providing more intensive practice to improve students' accuracy and understanding in the number conversion process.